Modeling of dual-band bandpass filter with triangular shaped DGS / Nur Wahida Miskon - Miskon, Nur Wahida (2017)
This thesis presents the design of dual-band bandpass filter with triangular shaped defective ground structure (DGS). The filter topology made up of a coupled line connected directly to line impedance with a same structure connected in parallel which produce a dual-path filter design. Triangular shaped DGS is added to the design in order to observe the changes in frequency response. It is found that the implementation of triangular shaped DGS improves the first passband with centre frequency of 1.086 GHz when compared with non DGS filter. The optimised size of the DGS is 150 mm2 located at the centre and at the quarter wavelength lines of the filter.